Bilateral cerebral oxygen saturation monitoring in carotid body tumour excision under general anaesthesia: a case report - Singh, Jagriti; Karandikar, Gayatri; Zirpe, Kaustubh; Govardhane, Balasaheb (International Journal of Research in Medical Sciences, 2023)
Carotid Body tumour is an uncommon non-chromaffin paraganglioma arising from chemoreceptor cells at the external and internal carotid artery bifurcation. The reported incidence is 1-2 cases per 1,00,000 population. Surgical excision is extremely difficult and possess challenges to both surgeon and the anaesthetist. We report here a case of CBT excision with the use of cerebral oximetry to reduce the chances of intra-operative cerebral ischemia.